Information literacy skills for preservice teachers: do they transfer to K-12 classrooms? - Stockham, Marcia G.; Collins, Heather (My University, 2012)
This study surveyed current education majors (n=70) in two Kansas universities to gain a perspective on their understanding of Information Literacy (IL) concepts and skills and to learn whether they anticipated teaching such concepts to their future K‐12 students. School Media Specialists in the state were also surveyed (n=85) and asked to share their observations of teachers new to the profession as to their understanding and practice of IL. Results indicate many education students were not familiar with IL concept terminology and at least some new teachers in the state do not have a clear understanding or priority for teaching such skills in K‐12 classrooms.
Keywords: Information literacy; Teacher education